Trocar blade-assisted scleral fixation for an incomplete dislocated intraocular lens. Issue 11 (November 2021) - Liu, Laura; Wang, Nan-Kai; Chen, Yen-Po; Chen, Kuan-Jen; Chou, Hung-Da; Yu-Chuan Kang, Eugene; Yeung, Ling; Hwang, Yih-Shiou; Chen, Tun-Lu; Chen, Yi-Hsing; Wu, Wei-Chi; Lai, Chi-Chun; et al.
Abstract : An incomplete dislocated intraocular lens (IOL) is often treated with IOL exchange because the IOL subluxates posteriorly during surgery and makes it difficult to fixate the IOL in situ. A trocar blade used for 23-gauge vitrectomy was used to lift and stabilize the IOL–capsular complex. The IOL can then be fixated using a suture loop fixation technique, which was originally limited to patients with decentered IOL. The advantage of this technique is that it allows the remaining zonular fibers and IOL to be preserved. The modified technique using a trocar blade to assist scleral fixation allows the incomplete dislocated IOL to be retrieved and fixated with a simplified surgical procedure.